On JD-Fuzzy Ideal of BH-Algebra - Mhammed. E, Showq; ., . (International Journal of Engineering and Technology, 2018)
In this analysis, you think about the construct JD-fuzzy ideal of BH-Algebra and we can study a number of properties, theorem and that we can provide some examples then we gave the construct JD –fuzzy extension ideal.